Si and SiGe Nanowire for Micro-Thermoelectric Generator: A Review of the Current State of the Art - Li, You; Wang, Guilei; Akbari-Saatlu, Mehdi; Procek, Marcin; Radamson, Henry H. (Frontiers in Materials, 2021)
In our environment, large availability of wasted heat has been driven to search for methods to harvest heat for many years. As a reliable way for the energy supply, SiGe has been used for thermoelectric generators in space missions for decades. Recently, micro-thermoelectric generators (μTEG) turn out to be a promising way to supply energy for internet of things (IoT) by using daily waste heat. Combining the predominant CMOS compatibility with high electric conductivity and low thermal conductivity performance, Si nanowire and SiGe nanowire have been a candidate for μTEG. This review gives a comprehensive introduction of the Si, SiGe nanowires and their possibility for μTEG. The basic thermoelectric principles, materials, structures, fabrication, measurements and applications are discussed deep inside.